Model Mekanisasi dan Ekspansi Pasar Agroindustri Produk Unggulan Gula Merah sebagai Bahan Baku Alternatif Industri Pangan di Kediri Jawa Timur - Mizar, Muhammad Alfian; Sholihul Hadi , Mokh.; Juwita, Ratna; Sumarno, Sumarno (J-Dinamika : Jurnal Pengabdian Masyarakat, 2026)
The SMEs PT. Tiga Dewi Timur Raya and UD Al Mubarok in Kediri produce sugarcane-based palm sugar and brown sugar as local superior products. The demand for palm sugar continues to increase along with consumer awareness of natural food products. The main problems faced by the partners include low production mechanization, busness management, and market access. The objective of the program is to enhance production capacity, sales turnover, and marketing management through the implementation of appropriate technology and business mentoring. This activity supports the Merdeka Belajar Kampus Merdeka (MBKM) program and the Key Performance Indicators (IKU) related to research downstreaming, lecturer involvement, and student entrepreneurship experience. The program activities included the redesign and application of appropriate technology, such as a Cabinet Dryer Mobility Rack for SME 1 and a Kerek Unloading Machine for SME 2. Training on production layout, work safety, and student focus group discussions (FGD) were also conducted. The program further focused on machine technical specifications, business management assistance, product catalogs, marketplace utilization, commercial website development, and innovation in converting sugarcane bagasse into animal feed. As a result, there were significant improvements in production technology, business management, and marketing strategies, along with academic recognition for students through industrial internships and independent project courses.